#1LIB1REF : ANALISIS ISI PESAN ADVOKASI DIGITAL SATU PUSTAKAWAN SATU REFERENSI (ONE LIBRARIAN ONE REFERENCE) DI TWITTER - Zuntriana, Ari (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2023)
1Lib1Ref (One Librarian, One Reference) is a movement to add references to Wikipedia articles that still need adequate references. 1Lib1Ref is currently open for participation by librarians and the general public. Wikipedia considers librarians to have good skills and resources to support the quality and reliability of articles. During the activity period of January 15 to February 5 and May 15 to June 5 every year, supporters of this program also campaign #1Lib1Ref on social media, especially Twitter (X). The researcher applies the content analysis method to analyze 214 tweets containing the hashtag #1Lib1ReF on Twitter in 2022. From the analysis results, 4 (four) big themes often appeared during that year, namely the #1LibRef campaign, event promotion, regional sentiment, and sharing personal experiences.